Diagnostic Approach to Pediatric Autoimmune Neuropsychiatric Disorders Associated With Streptococcal Infections (PANDAS): A Narrative Review of Literature Data - Prato, Adriana; Gulisano, Mariangela; Scerbo, Miriam; Barone, Rita; Vicario, Carmelo M.; Rizzo, Renata (Frontiers in Pediatrics, 2021)
Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) are clinical conditions characterized by the sudden onset of obsessive–compulsive disorder and/or tics, often accompanied by other behavioral symptoms in a group of children with streptococcal infection. PANDAS-related disorders, including pediatric acute-onset neuropsychiatric syndrome (PANS), childhood acute neuropsychiatric symptoms (CANS), and pediatric infection triggered autoimmune neuropsychiatric disorders (PITANDs), have also been described. Since first defined in 1998, PANDAS has been considered a controversial diagnosis. A comprehensive review of the literature was performed on PubMed and Scopus databases, searching for diagnostic criteria and diagnostic procedures of PANDAS and related disorders. We propose a test panel to support clinicians in the workout of PANDAS/PANS patients establishing an appropriate treatment. However, further studies are needed to improve our knowledge on these acute-onset neuropsychiatric conditions.